Podnebne spremembe in poplavna ogroženost urbanih območij z lastnimi padavinskimi vodami - Krajnc, Uroš (Gradbeni vestnik, 2019)
In most Central European cities, combined sewage systems are built. The overflows of combined sewage systems have the following causes: under dimensioned systems, extraordinary precipitation and poorly maintained systems. Climate changes are manifested in the increasing extreme precipitation that combined sewage systems are not able to drain. That's why we have floods in cities, including fatalities. Several strategies for mitigating these problems (green cities, smart cities, water wise cities, blue-green infrastructure) have a common goal to reduce the rainwater peak. Measures are available such as green roofs, separate drainage of wastewater and rainwater, retention and precipitation of rain waters. There are engineering tools (mathematical models) for planning construction measures by modelling the simultaneous flow of rainwater in the sewer system and surface. The key problems for implementing the necessary measures are the financing of these works and the spatial problems where these facilities are to be located.
Keywords: climate changes; floods in cities; green roofs; kanalizacija; mathematical models; modeliranje odtoka; operational programme for the discharge and treatment of urban wastewater; operativni program odvajanja in čiščenja komunalne odpadne vode; podnebne spremembe; poplave v mestih; sewage system; zelene strehe